The relationship between perceived social support and positive mental health among students at the University of Sarajevo - Faculty of Health Studies – A cross-sectional study (Journal of Health Sciences, 2025)
Introduction: Social support is very important in the educational transition for the promotion of well-being and transition among students of all ages, cultural identities, and educational levels. Support from parents, friends, teachers, and other relevant persons contribute to the academic, social, and emotional development of 1st-year undergraduate students.Methods: A cross-sectional study was conducted. The convenience sampling method was used to determine the sample. The research included 148 students of the 1st year of the first cycle of studies at the Faculty of Health Studies. The instruments used in the research are the Multidimensional Scale of Perceived Social Support Questionnaire and the Mental Health Questionnaire-Short Form.Results: Out of the total number of respondents, n = 126 (85.10%) perceived a high level, n = 17 (11.50%) a moderate level, while n = 5 (3.40%) a low level of social support. Out of the total number of 148 respondents, n = 70 (47.30%) belonged to the category of high positive mental health, n = 67 (45.30%) belonged to the category of moderate positive mental health, while n = 11 (7.40%) of the respondents characterized their mental health as low positive mental health. It was established that there is a medium-strong relation, with a positive sign, in correlation between positive mental health and perceived social support.Conclusion: The research results indicate a direct connection between perceived social support and positive mental health in the 1st year of the first cycle of University of Sarajevo-Faculty of Health Studies students, which indicates the importance of providing social support as an important resource for preserving the mental health of students during their studies.